Zweitsprachenerwerbsforschung und Fremdsprachendidaktik - Sopata, Aldona (Glottodidactica, 2007)
The aim of this paper is to explore main approaches to Second Language Acquisition. In particular, current research within the linguistic, sociolinguistic and cognitive approach is presented. The paper aims at demonstrating the relevance of the studies to foreign language pedagogy.